Who is Michael Jordan? - Anderson, Kirsten (Kirsten Stephanie) (2019)
Meet the man who changed the game forever. Michael Jordan has always been competitive--even as a young boy, he fought for attention. His need to be the best made him a star player on his college basketball team and helped him become an NBA legend, both for his skills and his endorsements. His Nike contract for Air Jordan basketball shoes set an unmatched precedent for professional athletes.
Who is Michael Jordan? -- Too short -- Carolina Blue -- Love of the game -- The rookie -- Trust no one -- Three-peat -- Now batting . . . Michael Jordan -- Three-peat, part 2 -- Wizard -- The greatest -- Timelines -- Bibliography.
Includes bibliographical references.
Age 8-12
Keywords: Jordan, Michael, -- 1963- -- Juvenile literature; Basketball players -- United States -- Biography -- Juvenile literature; African American basketball players -- Biography -- Juvenile literature